عوامل قوة الجيش الاشوري - هاشم, ازهار (University of Eloued جامعة الوادي, 2021)
إن من أهم المظاهر البارزة في حياة وتاريخ الإمبراطورية الآشورية هو القوة العسكرية ، فقد كان تاريخ الملوك الآشوريين عبارة عن سلسلة من الحملات العسكرية الى مختلف الجهات ولا سيما في الألف الأول قبل الميلاد لذا كان اعتماد الدولة الآشورية على جيشها المنظم والمزود بأقوى وأحسن الأسلحة ، وكان الجيش الآشوري من أكثر الجيوش كفاءة في العالم حيث كان بالإمكان استدعاء الرجال القادرين على القتال كافة في ظروف استثنائية جدا . One of the most prominent manifestations in the life and history of the Assyrian Empire is military power, the history of the Assyrian kings was a series of military campaigns to various sides, especially in the first millennium BC So the Assyrian state relied on its organized army and equipped with the strongest and best weapons, and the army The Assyrians are one of the most efficient armies in the world where men who were able to fight in all exceptional circumstances could be summoned. In this paper, we reviewed aspects of the military reforms introduced by the Assyrian kings that helped to establish the Assyrian Empire.
مقال
Keywords: قوة ; الجيش ; الاشوري ; حملات عسكرية